Knowledge, Attitudes, and Practices Related to Preoperative Chemoradiotherapy in Rectal Cancer Patients. (27th September 2016) - Chen, Xingxing; Lin, Ruifang; Li, Huifang; Su, Meng; Zhang, Wenyi; Deng, Xia; Zhang, Ping; Zou, Changlin
Abstract : Background . The aim of this study is to assess the knowledge, attitudes, and practices related to pre-CRT in patients of stage II/III rectal cancer. Materials and Methods . Questionnaires regarding the knowledge, attitudes, and practices of pre-CRT were mailed to 145 rectal cancer patients in II/III stage between January 2012 and December 2014, and 111 agreed to participate and returned completed questionnaires to the researcher. Logistic regression model was used to compare sociodemographic characteristics, knowledge, and attitude with practice, respectively. Results . A total of 145 patients were approached for interview, of which 111 responded and 48.6% (54) had undergone pre-CRT. Only 31.5% of the participants knew that CRT is a treatment of rectal cancer and 39.6% were aware of the importance of CRT. However, the vast majority of participants (68.5%) expressed a positive attitude toward rectal cancer. Multivariate logistic regression analysis revealed that knowledge level (p = 0.006 ) and attitudes (p = 0.001 ) influence the actual practice significantly. Furthermore, age, gender, and income were potential predictors of practice (allp < 0.05 ). Conclusion . This study shows that, despite the fact that participants had suboptimal level of knowledge on rectal cancer, their attitude is favorable to pre-CRT. Strengthening the professional health knowledge and realizing the importance of attitudes may deepen patients' understanding of preoperative therapy.